2011
DOI: 10.1002/art.30314
|View full text |Cite
|
Sign up to set email alerts
|

The anti-CD20 antibody rituximab reduces the Th17 cell response

Abstract: Objective. Rituximab has been shown to be successful in the treatment of rheumatoid arthritis (RA), and this unexpected finding indicates that B cells have an important role in this disease. The present study was undertaken to investigate the mechanism of action of rituximab in RA.Methods. Twelve patients with active RA were treated with rituximab. Disease activity was evaluated using the 28-joint Disease Activity Score. Synovial biopsy samples obtained at baseline and 12 weeks after treatment initiation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 34 publications
6
104
0
3
Order By: Relevance
“…Our findings are therefore consistent with demonstrations that B-cell depletion in lupus or rheumatoid arthritis patients dramatically decreases T-cell inflammation, including Th17 function (34,35). Our data also indicate myeloid cells play supportive, albeit disease-independent, roles in overall levels of T-cell inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are therefore consistent with demonstrations that B-cell depletion in lupus or rheumatoid arthritis patients dramatically decreases T-cell inflammation, including Th17 function (34,35). Our data also indicate myeloid cells play supportive, albeit disease-independent, roles in overall levels of T-cell inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…Second, rituximab affects regulatory elements of B cells positive for CD20 that are implicated in innate immunity and affects Th17 cells. [28][29][30][31] Finally, preliminary observations suggest that rituximab reduces expression of soluble urokinase-type plasminogen activator receptor by monocytes (Ghiggeri, personal observation). This is of particular importance because this receptor has recently been identified as a circulating factor that plays a direct pathogenetic role in FSGS by interacting with b3 integrin.…”
Section: Discussionmentioning
confidence: 99%
“…It is also of interest that both SMPDL-3b and ASM are expressed on Th17 (44), a cell lineage whose activation is considered a key element in the pathogenesis of nephrotic syndrome (6). Other studies also demonstrated that rituximab reduces Th17 cell response in rheumatoid arthritis (45), thus making a logical connection among rituximab, Th17, and nephrotic syndrome.…”
Section: Implications For Researchmentioning
confidence: 99%